The Origin of Viruses: Advancement in Prevention, Diagnosis and Treatment of Infectious and Somatic Diseases - Vladyko A.S. (Disease and Health: Research Developments Vol. 4, 2025)
Viruses are extremely abundant and diverse parasites of cells. They might have arisen during an early phase of the evolution of life on Earth dominated by RNA or RNA-like macromolecules, or when a cellular world was already well established. It has been assumed that the virus appears from adaptogens circulating in prokaryotes (bacteria, archaea, etc.) in the form of complexes of molecular motifs designed to adapt mammals to changing environmental conditions. Here the mechanisms of the emergence of coronavirus as one of the crucial stages of the adaptation process of virus formation from adaptogens and its impact on the further development of mammals, including humans was discussed. It also discusses what new things can be done for the prevention, diagnosis and treatment of both infectious and somatic diseases.